Cover Feature: Selective Oxygen and Hydrogen Functionalization of the h‐BN/Rh(111) Nanomesh (Chem. Eur. J. 52/2021). Issue 52 (18th August 2021) - Marie Freiberger, Eva; Späth, Florian; Bauer, Udo; Düll, Fabian; Bachmann, Philipp; Steinhauer, Johann; Hemauer, Felix; Waleska, Natalie J.; Schwaab, Valentin; Steinrück, Hans‐Peter; Papp, Christian
Abstract : By using an atomic hydrogen source and a supersonic molecular beam of oxygen, the hexagonal boron nitride nanomesh on Rh(111) was covalently functionalized with molecular oxygen and atomic hydrogen. Investigation of the system by high‐resolution X‐ray photoelectron spectroscopy reveals that only the pores of the nanomesh are functionalized whereas the wires remain unaffected. This selectivity leads to spatially defined chemical functionalization of the corrugated two‐dimensional material. More information can be found in the Full Paper by C. Papp et al. (DOI: 10.1002/chem.202101946 ).